Association of extreme heat events with sleep and cardiovascular health: a scoping review - Nathan Ashe; Sarah Wozniak; Malcolm Conner; Rayan Ahmed; Olivia Keenan; Michelle R. Demetres; Nour Makarem; Parisa Tehranifar; Rajalakshmi Nandakumar; Arnab K. Ghosh (Systematic Reviews)
Abstract Background Extreme heat events (EHEs), driven by anthropogenic climate change, exacerbate the risk of cardiovascular disease (CVD), although the underlying mechanisms are unclear. A possible mechanism leading to heat-related CVD is disturbances in sleep health, which can increase the risk of hypertension, and is associated with ideal cardiovascular health. Thus, our objective was to systematically review the peer-reviewed literature that describes the relationship between EHEs, sleep health, and cardiovascular measures and outcomes and narratively describe methodologies, evidence, and gaps in this area in order to develop a future research agenda linking sleep health, EHEs, and CVD. Methods A comprehensive literature search was performed in the following databases from inception–June 2023: Ovid MEDLINE, Ovid Embase, CINAHL, Web of Science, and the Cochrane Library. Studies retrieved were then screened for eligibility against predefined inclusion/exclusion criteria. Then studies were described qualitatively in relation to study design, findings, and the evidence linking the relationship between sleep health, EHEs, and CVD. Results Of the 2035 records screened, only three studies met the inclusion criteria. In these three studies, EHE was measured as absolute temperatures (greater than 30 °C) or relative temperatures (i.e., 90th percentile daily maximum temperature within the region). Cardiovascular (CV) measures described included blood pressure (BP), heart rate (HR), and HR variability (no CVD outcomes were described), and objective and subjective measurements of sleep health outcomes included sleep duration, calmness, ease of falling asleep, ease of awakening, freshness after awakening, and sleep satisfaction. Two studies were controlled trials, and one was a cohort study. During EHEs, individuals slept for shorter periods of time and less efficiently, with greater degrees of HR variability in two of the three studies lasting at most 1–2 days; BP (both systolic and diastolic) significantly decreased during EHEs in two of the studies. No formal assessment of a mediating relationship between EHE exposure, sleep outcomes, and CV measures was undertaken. Conclusions Few studies examine the link between CVD, sleep, and extreme heat as a possible mechanism of elevated CVD risk during EHEs, despite a strong physiological rationale. Our findings highlight an important gap in the literature that should be closely examined as EHEs become more frequent and their harmful impacts of health increase.